Advances in image and graphics technologies : 12th Chinese conference, IGTA 2017, Beijing, China, June 30-July 1, 2017, Revised selected papers /: 12th Chinese conference, IGTA 2017, Beijing, China, June 30-July 1, 2017, Revised selected papers. ([2018]) - Unknown
No abstract available